Action prediction modulates both neurophysiological and psychophysical indices of sensory attenuation - Roussel, Cédric; Hughes, Gethin; Waszak, Florian (Frontiers in Human Neuroscience, 2014)
Sensory attenuation refers to the observation that stimuli that are predicted based on one’s action are attenuated. This phenomenon, has primarily been observed as a neurophysiological phenomenon, with reduced ERP (e.g. Baess et al., 2008) and BOLD (e.g. Blakemore et al., 1998). In parallel, psychophysical investigations (e.g. Sato, 2008; Cardoso-Leite et al., 2010, Roussel et al., 2013) have confirmed that action prediction also influences psychological processing of sensory action effects. The present study recorded both of these phenomena in a single experiment, to confirm whether neurophysiological and psychophysical measures of sensory action effects are related. In addition, by measuring the ERP modulations of both stimulus contrast and prediction congruency, we sought to directly relate this neurophysiological phenomenon to the magnitude of sensory processing in the brain. Participants performed left- and right-hand voluntary actions that were previously associated with the letters A and H. In the test, phase participants were presented with these same two letters, at one of two possible contrasts. Participants were required to report which of the two possible contrasts had been presented. We observed both reduced contrast discrimination (in line with Roussel et al., 2013) and a reduced ERP response for congruent action-effects. Furthermore, our congruency modulation was observed on the same component that differed as a function of stimulus contrast. Taken together these results strongly suggest that neurophysiological indices of sensory attenuation reflect reduced sensory processing of voluntary action effects.